2006
DOI: 10.4049/jimmunol.177.1.566
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Plays an Important Role in the Development of Experimental Autoimmune Encephalomyelitis

Abstract: IL-17 is a proinflammatory cytokine that activates T cells and other immune cells to produce a variety of cytokines, chemokines, and cell adhesion molecules. This cytokine is augmented in the sera and/or tissues of patients with contact dermatitis, asthma, and rheumatoid arthritis. We previously demonstrated that IL-17 is involved in the development of autoimmune arthritis and contact, delayed, and airway hypersensitivity in mice. As the expression of IL-17 is also augmented in multiple sclerosis, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
1,094
5
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 1,414 publications
(1,178 citation statements)
references
References 54 publications
54
1,094
5
11
Order By: Relevance
“…Il17 –/– mice show significantly reduced severity in various inflammatory and autoimmune disease models, such as collagen‐induced arthritis,6 Il1rn −/− mouse arthritis,7 EAE8 and imiquimod (IMQ)‐induced skin inflammation,9, 10 suggesting critical roles of IL‐17 in inflammatory/autoimmune diseases. γδ 17 cells are detected in inflamed tissues of these disease models.…”
Section: The Pathogenic Roles Of γδ17 Cells In Mouse Inflammatory Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Il17 –/– mice show significantly reduced severity in various inflammatory and autoimmune disease models, such as collagen‐induced arthritis,6 Il1rn −/− mouse arthritis,7 EAE8 and imiquimod (IMQ)‐induced skin inflammation,9, 10 suggesting critical roles of IL‐17 in inflammatory/autoimmune diseases. γδ 17 cells are detected in inflamed tissues of these disease models.…”
Section: The Pathogenic Roles Of γδ17 Cells In Mouse Inflammatory Dismentioning
confidence: 99%
“…Mice deficient for IL‐17RA are highly susceptible to Klebsiella pneumoniae 3 and IL‐17‐deficient mice are susceptible to bacterial and fungal infection 4, 5. Interleukin‐17 is also implicated in various inflammatory/autoimmune disease models such as experimental autoimmune encephalomyelitis (EAE), arthritis in IL‐1 receptor antagonist‐deficient (Il1rn –/– ) mice and imiquimod‐induced psoriatic dermatitis in mice 6, 7, 8, 9, 10. Anti‐IL‐17 and anti‐IL‐17RA antibodies are effective to treat patients with psoriasis and psoriatic arthritis 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Helper CD4 + T cells that are characterized by the production of IL-17 are commonly called Th17 cells [1][2][3][4][5][6]. Th17 cells have features that are distinct from those of both Th1 and Th2 lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Th17 cells have features that are distinct from those of both Th1 and Th2 lineages. For example, TGF-b and IL-6 are required for the generation of Th17 cells, and IL-23 supports the survival and expansion of these cells [1][2][3][4][5][6][7][8]. Recent data also suggest that IL-6 and TGF-b drive initial lineage commitment of Th17 cells, whereas IL-23 mediates the full acquisition of pathogenic function of Th17 cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…autoimmune diseases including experimental autoimmune encephalomyelitis (EAE), a murine model of MS (Komiyama et al, 2006). Previous MS studies have also demonstrated increased amounts of IL-12p40 in the nervous system and increased IL-12 production by PBMC (Balashov et al, 1997;Comabella et al, 1998;Soldan et al, 2004).…”
mentioning
confidence: 99%